2021
DOI: 10.3390/ma14226944
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Optimization of Ultra High Performance Concrete for Improving Strength and Durability

Abstract: This paper seeks to optimize the mechanical and durability properties of ultra-high performance concrete (UHPC). To meet this objective, concrete specimens were manufactured by using 1100 kg/m3 of binder, water/binder ratio 0.20, silica sand and last generation of superplasticizer. Silica fume, metakaolin and two types of nano silica were used for improving the performances of the concrete. Additional mixtures included 13 mm long OL steel fibers. Compressive strength, electrical resistivity, mercury intrusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, the compressive strength difference between the CGS-0.7 and CGS-0.8 systems decreased from 14.2 MPa to 0.2 MPa when the W/C increased from 0.16 to 0.19. When the W/C ranged from 0.16 to 0.19, the compressive strength of the UHPC matrix for the CGS system was 1.5–6.6 MPa higher than that of the CQS system since the GBFS with higher reactivity could produce more hydration products and resulted in a denser microstructure of the UHPC matrix [ 31 , 32 ].…”
Section: Mechanical Properties Of the Uhpc Matrixmentioning
confidence: 99%
“…For example, the compressive strength difference between the CGS-0.7 and CGS-0.8 systems decreased from 14.2 MPa to 0.2 MPa when the W/C increased from 0.16 to 0.19. When the W/C ranged from 0.16 to 0.19, the compressive strength of the UHPC matrix for the CGS system was 1.5–6.6 MPa higher than that of the CQS system since the GBFS with higher reactivity could produce more hydration products and resulted in a denser microstructure of the UHPC matrix [ 31 , 32 ].…”
Section: Mechanical Properties Of the Uhpc Matrixmentioning
confidence: 99%
“…UHPC is durable and does not even need to be maintained for 80 years [25]. Regarding the application of nano additions, several contributions have noted that employing various cement substitutes could increase the mechanical qualities and durability [26]. Authors also have proved that cementitious materials' endurance can be further increased by adding SCMs through experiments [27].…”
Section: Introductionmentioning
confidence: 99%
“…Son et al [37] revealed that the addition of NS decreased the generation rate of metastable hydrates, maintaining the long-term strength of calcium aluminate cement. With the development of nanotechnology, the use of NS in concrete has grown in recent years [38,39]. Wang et al [40] demonstrated that NS-modified underwater concrete had higher compressive strength and lower permeability, contributing to resisting seawater attacks.…”
Section: Introductionmentioning
confidence: 99%